COVID-19: first 100 days of the communication policy by the Argentinean government - Mathot, Clarisa (Universidad Nacional de Villa María, 2022)
Political communication can be presented in various ways, the way in which it manifests itself in the web of social, political and institutional relationships in a given context requires planning and strategy. The impact and expansion worldwide, and in Argentina in particular, of COVID-19 generated consequences in the medium and long term, so it becomes imperative to think about the present. In this sense, in the article we will analyze how the communication policy of the Argentine Government was developed during the beginning of the COVID 19 Pandemic, how government communication, crisis and risk was developed during the period from March to June 2020, since the initial months are key for the development and impact of public policies in a health emergency situation.